Left Hemisphere Dominance for Negative Facial Expressions: The Influence of Task - Burgund, E. Darcy (Frontiers in Human Neuroscience, 2021)
Major theories of hemisphere asymmetries in facial expression processing predict right hemisphere dominance for negative facial expressions of disgust, fear, and sadness, however some studies observe left hemisphere dominance for one or more of these expressions. Research suggests that tasks requiring the identification of six basic emotional facial expressions (angry, disgusted, fearful, happy, sad, and surprised) are more likely to produce left hemisphere involvement than tasks that do not require expression identification. The present research investigated this possibility in two experiments that presented six basic emotional facial expressions to the right or left hemisphere using a divided-visual field paradigm. In Experiment 1, participants identified emotional expressions by pushing a key corresponding to one of six labels. In Experiment 2, participants detected emotional expressions by pushing a key corresponding to whether an expression was emotional or not. In line with predictions, fearful facial expressions exhibited a left hemisphere advantage during the identification task but not during the detection task. In contrast to predictions, sad expressions exhibited a left hemisphere advantage during both identification and detection tasks. In addition, happy facial expressions exhibited a left hemisphere advantage during the detection task but not during the identification task. Only angry facial expressions exhibited a right hemisphere advantage, and this was only observed when data from both experiments were combined. Together, results highlight the influence of task demands on hemisphere asymmetries in facial expression processing and suggest a greater role for the left hemisphere in negative expressions than predicted by previous theories.